Omnibus Law Undang-Undang Cipta Kerja dalam Perspektif Sosiologi Hukum - Wira Perdana, Fadjrin; Irwan, Irwan; Lumban Tungkup, Doharman; Miran, Miran; Siswanto, Wahyudi (Jurnal Indonesia Sosial Sains, 2022)
Omnibus Law is a method of legislation that combines various types of laws into one specific law to resolve statutory problems. One of the products of the Omnibus Law is the birth of the work copyright law which has caused a lot of polemics because it is considered a new legal policy in the formation of law in Indonesia. The purpose of this study is to examine the omnibus law, especially the Job Creation Act from the perspective of the sociology of law. This study uses a descriptive research method with a qualitative approach. Data was collected using a literature study. The results showed that the drafting of the Omnibus Law on the Job Creation Act did not heed sociological principles so it received resistance or rejection from the community component. One of the objectives of the establishment of the Omnibus Law on Job Creation is to support the economy and make it easier for investors to invest. This is very vulnerable to corrupt practices, therefore the government is urged to pay attention to the problem of eradicating corruption and related to human rights.